Mapping Talaqqi in International Literature: A Systematic Literature Review and Bibliometric Analysis with Opportunities for Technological Integration - Ade Putra Hayat; Ridha Ahida; Hairul Fauzi; Charles Charles; Yan Guspriadi (At- Ta'lim : Jurnal Pendidikan, 2026)
Talaqqi, a classical face-to-face method of transmitting Islamic knowledge that emphasizes sanad authenticity and meaningful teacher-student relationships, constitutes the cornerstone of traditional Islamic pedagogy. This study maps the intellectual structure and research landscape of talaqqi in international literature through a hybrid Systematic Literature Review and bibliometric analysis of 24 Scopus-indexed documents published between 2013 and 2026. Employing the PRISMA 2020 protocol along with VOSviewer and Biblioshiny, the findings reveal talaqqi as an emerging research field experiencing a significant paradigmatic shift. While remaining firmly rooted in classical principles of sanad, Qur’anic education, and interpersonal pedagogy, the literature demonstrates an inductive emergence of technology, digital platforms, and automated classification models. The study highlights substantial opportunities for hybrid learning frameworks that integrate traditional talaqqi practices with artificial intelligence and digital tools while preserving epistemological integrity. These results offer important theoretical contributions and practical implications for the development of technology-enhanced Islamic pedagogy in higher education institutions.